REVIEW OF THE CORRELATION BETWEEN SPECIFIC BIOMARKERS IN LEUKEMIA AND PERIODONTAL DISEASE IN CHILDREN - Adumitroaie Alina; Foia Liliana; Anistoroaei Daniela; Cioloca Daniel; Maftei George; Bogdan Maria; Vlad Cristiana; Toma Vasilica (Romanian Dental Association for Education, 2019)
Objectives: The purpose of this review was evaluating the literature regarding a possible correlation between biomarkers analyzed in children with leukemia and periodontal disease, with emphasis on the antioxidant activity and oxidative stress markers, observed also in leukemia and in periodontal disease. Materials and method: Articles from Medline database were evaluated, searched via PubMed using MeSH terms. Results: Since periodontal disease is a very common oral pathology in patients with leukemia, it is crucial to distinguish whether the modification of biochemical markers is caused by the alteration of immune general system, or the existent periodontal pathology. Conclusions: Regarding the significance of specific biomarkers seen in children with leukemia and periodontal disease, further studies are necessary to determine their interdependence and clinical relevance.